One-year impact of behavioural interventions on schistosomiasis-related knowledge, attitude and practices of primary schoolchildren in Pemba, Tanzania - Naomi C. Ndum; Lydia Trippler; Sarah O. Najim; Anisa S. Ali; Jan Hattendorf; Shaali M. Ame; Fatma Kabole; Jürg Utzinger; Said M. Ali; Stefanie Knopp (Infectious Diseases of Poverty)
Abstract Background Elimination of schistosomiasis as a public health problem and interruption of transmission in selected areas are goals set by the World Health Organization for 2030. Behaviour change communication (BCC), coupled with other interventions, is considered an essential measure to reduce the transmission of Schistosoma infection. Focusing on elimination, we assessed the 1-year impact of BCC interventions on schistosomiasis-related knowledge, attitude and practices (KAP) of schoolchildren in hotspot schools versus low-prevalence schools that did not receive the interventions. Methods School-based cross-sectional surveys were implemented in 16 schools on Pemba Island, Tanzania, in 2020 and 2022, respectively. The schistosomiasis-related KAP were assessed in children attending grades 3–5, using pre-tested questionnaires. Between the surveys, in 2021, children from hotspot schools were exposed to BCC interventions. The difference in mean knowledge and attitude scores, respectively, between schoolchildren from hotspot and low-prevalence schools during the survey in 2022 was determined with a linear mixed-effect model. Results In the five hotspot schools that received BCC interventions, 315 children participated in the survey in 2020 and 349 in 2022. There was a 21.0% increase in children with moderate knowledge and a 13.8% decrease in no knowledge; a 8.3% increase in good attitude and a 19.2% decrease in poor attitude; 3.4% and 3.2% fewer children reported to use waterbodies for washing clothes or body, respectively. In the 11 low-prevalence schools without BCC interventions, 778 children participated in 2020 and 732 in 2022. The percentage of children with poor knowledge (56.4% and 63.1%) and poor attitude (55.3% and 53.1%) remained relatively stable from 2020 to 2022, but 4.9% and 3.0% less children reported to use waterbodies for washing clothes or their body, respectively. In 2022, the difference in mean knowledge scores was 0.8 [95% confidence interval (CI): 0.5−1.1] and the difference in mean attitude scores was 0.6 (95% CI: 0.4−0.7) between children in hotspot compared with low-prevalence schools. Conclusions After one year of implementation, the BCC interventions markedly improved the KAP of exposed children. Complemented by improved access to clean water and sanitation, BCC holds promise to contribute successfully to the achievement of schistosomiasis control and elimination targets. Trial registration ISRCTN, ISRCTN91431493. Registered 11 February. 2020, https://www.isrctn.com/ISRCTN91431493 . Graphical Abstract